Conservative management and minimal intervention in patients with natal and neonatal teeth: Report of four cases - Carolina Pardo Hernández; Claudia Isabel Guerrero Torres; Laila Yaned González Bejarano (Revista de Odontopediatria Latinoamericana, 2022)
Natal and neonatal teeth are present at birth or in the first month of life. They are observed more frequently in the mandibular central incisors, and in most cases, these teeth represent the true primary teeth. Clinical characteristics, possible complications and the clinical course are parameters to consider for proper management. Nevertheless, different reports argue that complications may occur after extraction in newborns. To date, there are no documented cases reported in the literature describing complications in retained teeth, such as aspiration of a tooth. The objective of the present study is to introduce four cases, three of which were treated with conservative management. Considering that the prevalence has increased progressively in recent years, neonatologists and pediatric dentists must make an early diagnosis and offer adequate treatment, providing general and oral wellness for each patient. The success of the treatment depends on periodic follow-up.